2021
DOI: 10.1177/1545968321999053
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Task Effects During a Motor-Cognitive Task in Parkinson’s Disease: Patterns of Prioritization and the Influence of Cognitive Status

Abstract: People with Parkinson’s disease (PD) experience greater difficulties during dual task (DT) walking compared to healthy controls, but factors explaining the variance in DT costs remain largely unknown. Additionally, as cognitive impairments are common in PD it is important to understand whether cognitive status influences the strategies used during DT paradigms. The study aimed to (1) explore DT costs on gait and cognition during DT walking, (2) investigate factors associated with DT costs, and (3) to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…Al-Yahya's et al meta-analysis [37] showed that in healthy individuals there is a strong association between age and decreased gait speed during dual tasks and between cognitive level and decreased gait speed during dual tasks. In the study by Johansson et al [38], it was observed that the performance of the dual task generated a deterioration in a significant percentage of the variables associated with gait, while without observing variations in symmetry, as we also observed in our study. These authors also observed a longer reaction time during the dual task and also with significant individual variability, which reached a deterioration of almost 40% in some individuals [38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Al-Yahya's et al meta-analysis [37] showed that in healthy individuals there is a strong association between age and decreased gait speed during dual tasks and between cognitive level and decreased gait speed during dual tasks. In the study by Johansson et al [38], it was observed that the performance of the dual task generated a deterioration in a significant percentage of the variables associated with gait, while without observing variations in symmetry, as we also observed in our study. These authors also observed a longer reaction time during the dual task and also with significant individual variability, which reached a deterioration of almost 40% in some individuals [38].…”
Section: Discussionsupporting
confidence: 90%
“…In the study by Johansson et al [38], it was observed that the performance of the dual task generated a deterioration in a significant percentage of the variables associated with gait, while without observing variations in symmetry, as we also observed in our study. These authors also observed a longer reaction time during the dual task and also with significant individual variability, which reached a deterioration of almost 40% in some individuals [38]. De Oliveira Silva et al [39] suggest that poor DT and spatial navigation abilities are present in partial functional de-pendence in instrumental activities of daily living, and these tasks should be considered as a functionality screening tool in patients with dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Within the EXPANd trial, participants were assessed with a large neuropsychological test battery comprising the domains executive function, attention/working memory, episodic memory, and visuospatial functions ( Franzén et al, 2019 ). This test battery enabled the classification of mild cognitive impairment, previously described by Johansson and colleagues ( Johansson et al, 2021 ). In this study we focused on the following scales to assess cognition and executive function: the Delis-Kaplan Executive Function System (D-KEFS) ( Fine and Delis, 2011 ), the Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV) ( Wechsler, 1955 ), and MoCA ( Borland et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Spatiotemporal data were computed from all the steps recorded during the entire task. As previously reported (Johansson et al 2021;Vitorio et al 2021), to characterize the performance of usual and DT walking, the DT cost ([dual task − single task)/single task] × 100) was The order of the task was randomly assigned calculated for two key measurements (Morris et al 1998) of walking (i.e. gait speed and stride length).…”
Section: Gait Performancementioning
confidence: 99%